Emerging evidence of genotype–phenotype associations of developmental and epileptic encephalopathy due to KCNC2 mutation: Identification of novel R405G - Wang, Sumei; Yu, Yejing; Wang, Xu; Deng, Xiaolong; Ma, Jiehui; Liu, Zhisheng; Gu, Weiyue; Sun, Dan (Frontiers in Molecular Neuroscience, 2022)
Developmental and epileptic encephalopathies (DEEs) have high genetic heterogeneity, and DEE due to the potassium voltage-gated channel subfamily C member 2 (KCNC2) variant remains poorly understood, given the scarcity of related case studies. We report on two unrelated Chinese patients, an 11-year-old boy and a 5-year-old girl, diagnosed with global developmental delay (GDD), intellectual disability (ID), and focal impaired awareness seizure characterized by generalized spike and wave complexes on electroencephalogram (EEG) in the absence of significant brain lesions. Whole-exome sequencing (WES) and electrophysiological analysis were performed to detect genetic variants and evaluate functional changes of the mutant KCNC2, respectively. Importantly, we identified a novel gain-of-function KCNC2 variant, R405G, in both patients. Previously reported variants, V471L, R351K, T437A, and T437N, and novel R405G were found in multiple unrelated patients with DEE, showing consistent genotype–phenotype associations. These findings emphasize that the KCNC2 gene is causative for DEE and facilitates treatment and prognosis in patients with DEE due to KCNC2 mutations.